Note: The Effect of Silo Milk Composition Parameters on Heat Stability of Whole Milk Powder - Negri Rodriguez, Livia Maria; Chavez Clemente, Monica Silvina; Taverna, Miguel Angel; Cuatrin, Alejandra; Rubiolo, Amelia Catalina (Sage Publications, 2019)
The aim of this work was to study silo raw milk (SRM) compositional parameters that affect the heat stability of whole milk powder (WMP). Seasonal changes of heat stability from SRM and WMP were also characterised. Silo raw milk samples and the corresponding WMP samples were collected twice a month from a local factory from April 2000 to April 2001. Silo raw milk heat coagulation time (HCT), urea and lactose concentrations were found to contribute to milk powder HCT statistical model (R2 = 0.72). High HCT values during summer and low ones during spring were detected for both SRM and WMP samples. Heat coagulation time values of SRM were always higher than those measured in their powders, due to the effects of processing conditions on heat stability